Total hip replacement with the CLS expansion shell and a structural femoral head autograft for patients with congenital hip disease - Rozkydal, Zbynyk; Janícek, Pavel; Smíd, Zdenyk (The Journal of bone and joint surgery. American volume, 2005)
BACKGROUND: Reconstruction of a dysplastic acetabulum in a patient with osteoarthritis of the hip may be accomplished with a variety of surgical techniques. The aim of our study was to assess the outcomes of total hip replacement with the uncemented CLS expansion shell and a structural femoral head autograft to augment the deficient acetabulum in patients with osteoarthritis secondary to congenital hip disease. METHODS: Between 1990 and 1994, we used a CLS expansion shell with a structural femoral head autograft in forty-three consecutive patients (forty-three hips) with osteoarthritis secondary to congenital hip disease. The ratio of male to female patients was 5:38, and the mean age of the patients was forty-eight years. According to the preoperative radiographic assessment, the dysplasia was categorized as Crowe type I in six patients, Crowe type II in thirty-one patients, and Crowe type III and type IV in three patients each. No patient was lost to follow-up. The mean duration of follow-up was 120 months. Plain radiographs were made immediately after surgery and at the latest follow-up evaluation. Clinical outcomes were determined with use of the Harris hip score and the Merle d'Aubigné and Postel score, and a radiographic analysis was performed. RESULTS: Postoperatively, the mean Harris hip score had improved 58 points for patients with Crowe type-I and II dysplasia, 47 points for patients with Crowe type-III dysplasia, and 46 points for patients with Crowe type-IV dysplasia (p < 0.05 for all). At the latest follow-up examination, the mean Harris hip score for all patients was 92.6 points. The mean Merle d'Aubigne and Postel score was 8.3 points preoperatively and 15.8 points at the time of the latest follow-up. The mean coverage of the shell by the graft immediately after surgery was 32.2%. Osteointegration of the CLS expansion shell was evident radiographically in all forty-three hips at the latest follow-up evaluation. There were no failures of the bone grafts. Clinical survival of the CLS expansion shell with a structural femoral head autograft was 100% at a mean of ten years after surgery. The rate of survival of the shell, with radiographic signs of loosening as the end point, was 88.2% at ten years. CONCLUSIONS: The CLS uncemented expansion shell, when used with a structural femoral head autograft, provides a reliable reconstruction, augments deficient acetabular bone stock, and allows placement of the socket at or close to the anatomic center of hip rotation in patients undergoing total hip arthroplasty to treat the sequelae of congenital hip disease.
Keywords: Acetabulum; náhrada kyčelního kloubu; Femur; Arthroplasty, Replacement, Hip; Retrospective Studies; artróza kyčelních kloubů; Osteoarthritis, Hip; výsledek terapie; acetabulum; Middle Aged; mužské pohlaví; kyčelní protézy; vývojová kyčelní dysplazie; Adult; Transplantation, Autologous; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; Hip Dislocation, Congenital; Hip Prosthesis; autologní transplantace; femur; dospělí; Female; Treatment Outcome; lidé; Male